1995
DOI: 10.1055/s-0038-1649921
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Phylioquinone (Vitamin K1) Concentrations in Hemodialysis Patients

Abstract: SummaryIntra- and interindividual variation of phylloquinone (vitamin K1) concentrations was investigated by repeat analysis of serum from 28 hemodialysis patients with different apolipoprotein E genotypes. Phylloquinone concentrations ranged from 0.1 to 9.0 nM, with a mean of 1.08 nM (standard deviation 1.90 nM).Most of the variation in serum phylloquinone concentrations was due to differences between patients; the ratio of intra-to interindividual variation was 0.17. Serum triglyceride concentrations and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…7,[9][10][11][12] These findings were independent of CYP2C9 polymorphisms, the VKORC1 1173C/T variant, and numerous other factors that can alter warfarin dose requirements. The results were statistically significant among African Americans but not Caucasians; however, the e4 allele was less common among Caucasians, which could have limited our ability to detect an effect in this group.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…7,[9][10][11][12] These findings were independent of CYP2C9 polymorphisms, the VKORC1 1173C/T variant, and numerous other factors that can alter warfarin dose requirements. The results were statistically significant among African Americans but not Caucasians; however, the e4 allele was less common among Caucasians, which could have limited our ability to detect an effect in this group.…”
Section: Discussionmentioning
confidence: 76%
“…Sconce et al 16 found that the e4 allele was associated with lower doses in a Caucasian population, but, interestingly, e4 carriers had the highest plasma vitamin K concentrations, not the lowest as might be expected. [10][11][12] Clearly, the relationship between APOE genotype and warfarin dose requirements is complex; further study is needed to better understand the interactions between APOE and race, other genotypes, diet and vitamin K levels. In a retrospective study of different anticoagulants, acenocoumarol and phenprocoumon, Dutch Caucasian e4 carriers and homozygotes required a significantly lower mean dose of acenocoumarol, but not of phenprocoumon, relative to e3/e3 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been suggested that vitamin K status in hemodialysis patients is also influenced by the apolipoprotein E genotype. Lipoprotein-bound apolipoprotein E regulates the clearance of circulating vitamin K in the liver and in peripheral tissues (33). It is interesting to note that the vitamin K requirement in extrahepatic tissues (for ␥-glutamyl carboxylation of MGP, for example) appears to be greater than that for the liver itself (for the modification of coagulation factors).…”
Section: Discussionmentioning
confidence: 99%
“…This intestinal absorption involves the solubilization of vitamin K into mixed micelles composed of bile salts and products of pancreatic lipolysis and is known to be impaired in patients with malabsorption or other gastrointestinal disorders, including biliary atresia, cystic fibrosis, celiac disease, and short bowel syndrome [12]. Vitamin K is not known to have a carrier protein; instead, triglyceride-rich lipoproteins (TRL), primarily chylomicron remnants and very low-density lipoproteins (VLDL), are thought to be the main transporters of phylloquinone [13][14][15]. Vitamin K is extensively metabolized in the liver and excreted in the urine (20%) and bile (40%).…”
Section: Introductionmentioning
confidence: 99%